2012
DOI: 10.1371/journal.pntd.0001603
|View full text |Cite
|
Sign up to set email alerts
|

A Research Agenda for Helminth Diseases of Humans: Social Ecology, Environmental Determinants, and Health Systems

Abstract: In this paper, the Disease Reference Group on Helminth Infections (DRG4), established in 2009 by the Special Programme for Research and Training in Tropical Diseases (TDR), with the mandate to review helminthiases research and identify research priorities and gaps, focuses on the environmental, social, behavioural, and political determinants of human helminth infections and outlines a research and development agenda for the socioeconomic and health systems research required for the development of sustainable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
86
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 64 publications
1
86
0
4
Order By: Relevance
“…The places where children play are important for public health (9). In many studies, it has been demonstrated that parasitic infections have a considerable negative influence on health factors such as weight and height (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…The places where children play are important for public health (9). In many studies, it has been demonstrated that parasitic infections have a considerable negative influence on health factors such as weight and height (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Chile no está libre de este problema, clasificándose entre los países con mayor desigualdad en el mundo 3 . Las infecciones parasitarias son enfermedades asociadas a condiciones de desigualdad social, siendo más prevalentes en contextos de pobreza, hacinamiento, deficientes condiciones sanitarias, bajo nivel educacional y residencia en cordones urbano marginales y rurales 4 . Múltiples estudios identifican factores sociales, económicos, culturales y sanitarios asociados a parasitosis intestinal en niños 5,6 .…”
unclassified
“…Furthermore, parasitic intrinsic factors such as parasitemia and toxins produced during the growth and the reproduction of the parasite, coupled with several host factors such as malnutrition, lifestyle, comorbidities and immunosuppression or other conditions like pregnancy, are important clues to predict the outcome of infection [22].…”
Section: Discussionmentioning
confidence: 99%